Snail mediates PDGF‐BB‐induced invasion of rat bone marrow mesenchymal stem cells in 3D collagen and chick chorioallantoic membrane1. Issue 9 (25th May 2013) - Lu, Changlian; Sun, Xiaojiao; Sun, Lijun; Sun, Jianping; Lu, Yan; Yu, Xin; Zhou, Lingyun; Gao, Xu
Abstract: We previously reported that membrane type‐1 matrix metalloproteinase (MT1‐MMP) enables mesenchymal stem cells (MSCs) to move through both three‐dimensional (3D) type I collagen and basement membrane barriers; however, its upstream regulating factors were unidentified. Here, we report that PDGF‐BB upregulates both mRNA and protein expression of snail in rat bone marrow MSCs (rBMMSCs). PDGF‐BB enhances rBMMSC invasion in 3D collagen, which is blocked by snail specific siRNA transfection. Snail overexpression induced by plasmid transfection results in increased rBMMSC invasion in 3D collagen. Snail expression induced by PDGF‐BB in MSCs is inhibited by LY294002 and PD98059, which are inhibitors of the PI3K/AKT and MAPK1/2/ERK1/2 signaling pathways, respectively. MT1‐MMP expression in rBMMSCs, both as mRNA and protein, is decreased by snail siRNA transfection, but increased by snail overexpression, indicating that they are controlled by snail. Finally, snail controls MSC transmigration through chorioallantoic membrane of 11‐day‐old chick embryos. Taken together, these in vitro and in vivo data identify snail as a critical mediator for rBMMSC invasion induced by PDGF‐BB. J. Cell. Physiol. 228: 1827–1833, 2013. © 2013 Wiley Periodicals, Inc.